Legal responsibility for corrupt practices with an impact on the enforcement of political accountability: Case study of Slovakia - Michal Lendvorský; Daniela Mališová; Bernard Pekár; Beáta Mikušová Meričková; Jana Štrangfeldová (Scientific Papers of the University of Pardubice, Series D: Faculty of Economics and Administration, 2021)
Tackling corruption regularly appears on the agendas of almost all governments. Anti-corruption public policies aim to prevent corrupt behaviour both at the highest levels of government and in everyday social life. On the one hand, corruption seriously undermines the democratic principles of the rule of law; on the other hand, the enforceability of political accountability linked to the rule of law determines the level of corruption. The aim of the study is to identify the enforceability of legal responsibility for corrupt acts against public officials in the Slovak political arena during the electoral periods from 1994 to 2020. This objective is fulfilled by answering research questions focused on the incidence rate and definition of corrupt conduct in the Slovak Republic environment. The main method of the paper is a collective case study conducted on 219 cases. The results showed that the societal pressure for accountability of political accountability is increasing over time. Hence, the importance of anti-corruption public policy is growing, but its effectiveness remains questionable. The results of the research point to low levels of accountability, especially under left-wing governments.
Keywords: D73; K49; 330; Corruption; Rule of Law; Political Accountability; Anti-corruption policy